Modified Ant Colony Optimization Algorithm for Multiple-vehicle Traveling Salesman Problems - Yindee Oonsrikaw; Arit Thammano (My University, 2018)
Multiple-vehicle
Keywords: Vehicle Routing Optimization Methods